Korelasi Motivasi Ekstrinsik terhadap Murajaah Hafalan Al-Qur’an Alumni MUQ Pagar Air di UIN Ar-Raniry Banda Aceh - Maisar Hanifa; Musradinur (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2026)
The phenomenon of declining quality of Qur'an memorization in some alumni of Madrasah Ulumul Qur'an Pagar Air after continuing education at the university level. Based on the results of initial observations, many alumni faced various challenges, such as changes in learning patterns, lack of memorization guidance and weakened enthusiasm to maintain memorization. In addition, extrinsic motivations such as support from parents, teachers, peers, and the campus environment are suspected to have a significant role in the consistency of murajaah memorization of the Qur'an. This study aims to determine the relationship between extrinsic motivation and memorization of the Qur'an of alumni of Madrasah Ulumul Qur'an Pagar Air at UIN Ar-Raniry Banda Aceh. This study uses a quantitative approach with a correlational method. The research population is alumni of Madrasah Ulumul Qur'an Pagar Air who are studying in the Islamic Religious Education Study Program and the Qur'an and Tafsir Study Program. The research sample was 25 respondents who chose the purposive sampling technique. Based on the results of the regression test, a significant value of 0.674 > 0.05 was obtained, which showed that there was no relationship between extrinsic motivation and memorization of the Qur'an. Thus, it can be concluded that extrinsic motivation does not have a significant relationship with the process of memorizing the Qur'an in the alumni of Madrasah Ulumul Qur'an Pagar Air UIN Ar-Raniry Banda Aceh